A novel method for the quantitative characterization of the simultaneous plasticizing and filling performance in ultrasonic plasticization micro injection molding - Yang Zou; Wangqing Wu; Xiaotian Zhou; Guomeng Wei; Bingyan Jiang (Materials & Design, 2021)
A novel method is proposed for the quantitative characterization of the unique simultaneous plasticizing and filling phenomenon in ultrasonic plasticization micro-injection molding (UPMIM). The injection rate is redefined as the mass flow rate during the melt filling in the cavity. The shape of the cavity was designed as a mechanical test sample scaled down from the standard tensile specimen. The micro-molded specimens were subjected to tensile tests and Gel Permeation Chromatography (GPC) measurements to analyze their mechanical properties and possible macromolecular alterations, respectively. The influence of process parameters on the injection rate and mechanical properties was obtained by orthogonal and single factor experiments. The results show that the simultaneous plasticizing and filling process can be quantitatively characterized by the injection rate which is significantly affected by the plunger speed. With the capability of the present experimental setting, a maximum injection rate of 237 mg/s for polypropylene can be achieved via process optimization. Particularly, it was confirmed that higher injection rates can be utilized for increased molding efficiency while without undermining the mechanical properties of micro-molded specimens according to the tensile tests and GPC measurements.